Bio-Ecology of Predatory Coccinellid Beetle, Coccinella septempunctata (Coleoptera: Coccinellidae) and its Dynamics in Rice Field of Terai Region of West Bengal, India - Ghosh, S. K.; Chakraborty, K.; Mandal, T. (International Journal of Bio-resource and Stress Management, 2023)
Incidence of predatory coccinellid beetle, Coccinella septempunctata population in rice crop (Oryza sativa L.) was assessed by light trapping during four consecutive kharif crop seasons (2005-2008) at Cooch Behar, West Bengal. Mean duration of 1st, 2nd, 3rd and 4th larval instars C. septempunctata were 3.10±0.47, 4.20±0.48, 5.20±0.69 and 7.9±0.85 days respectively. Duration of total larval period was 20.4±0.73. While that of the pupal period was 5.10±0.53 days. Mean male and female emergence rate was 36.6±2.98% and 57.6±4.21%, respectively. Male to female sex ratio was 1:1.7±0.19. The food consumption of ladybirds was significantly higher in 4th instar grubs. Searching distance by ladybird beetle was significantly higher in case of 4th instar grubs. Grossly, C. septempunctata population was initiated at about 25 standard meteorological weeks (SMW), improved at first slowly up to 27 SMW then steadily up to 32 SMW attaining the maximum at about 34 SMW which was maintained up to about 37 SMW. The population then subsumed at first slowly up to 40 SMW then abruptly. Abiotic conditions such as minimum temperature, temperature gradient, maximum relative humidity and average relative humidity had significant positive influence on C. septempunctata population. In case of minimum relative humidity and sunshine hours, a negative influence was observed. In addition, other factors such as rainfall imparted insignificant positive effect on population development.